21st-Century Educational Leadership: A Review of Core Theories, Managerial Perspectives, and Emerging Trends - Bahtiar, Hikmanisa; Muhammad Kholidinna Qasabandiyah (Yayasan Cendekiawan Indonesia Timur, 2025)
Educational leadership is a key factor in improving the quality of learning, teacher professionalism, and the effectiveness of school and university organizations. This article aims to review the development of core educational leadership theory, the integration of management and business perspectives, and contemporary trends that shape 21st-century leadership. Using a scoping review approach, this study analyzes 30 selected articles published between 2019 and 2024, sourced from international databases (Scopus, Web of Science, Springer, Taylor & Francis, Sage, and ERIC). The articles were categorized into three groups: (1) core models of educational leadership such as instructional, strategic, spiritual, and emotional leadership; (2) interdisciplinary perspectives linking education with management theory, including governance, resource management, and empowerment leadership; and (3) contemporary trends in digital, global, innovative, and character-based leadership. The results of the review show that instructional and strategic leadership remain the main foundation, but are increasingly reinforced by organizational management theory and business innovation. In addition, the demands of globalization, digitalization, and social change have led to the emergence of new leadership models that are more collaborative, adaptive, and value-oriented. The implications of this study emphasize the importance of integrating classical theory, managerial insights, and contemporary trends to shape educational leaders who are capable of responding to the complexities of the modern era while preparing the research agenda for the future.